2021
DOI: 10.1093/jxb/erab278
|View full text |Cite|
|
Sign up to set email alerts
|

Rubisco substitutions predicted to enhance crop performance through carbon uptake modelling

Abstract: Improving the performance of the CO2-fixing enzyme Rubisco is among targets for increasing crop yields. Here, Earth system model (ESM) representations of canopy C3 and C4 photosynthesis were combined with species-specific Rubisco parameters to quantify the consequences of bioengineering foreign Rubiscos into C3 and C4 crops under field conditions. The “two big leaf” (sunlit/shaded) model for canopy photosynthesis was used together with species-specific Rubisco kinetics parameters including maximum rate (Kcat),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Furthermore, any increases in Rubisco CO 2 assimilation may benefit from additional modifications in downstream fluxes, for example the transport of carbohydrates to sink tissues ( Wang et al , 2020 ). Modified canopy-scale models that account for Rubisco parameters may help further to predict the physiological consequences of replacing native Rubiscos with heterologous enzymes in plants ( Iqbal et al , 2021 ).…”
Section: Rbcs As An Engineering Target For Enhancing Plant Photosynth...mentioning
confidence: 99%
“…Furthermore, any increases in Rubisco CO 2 assimilation may benefit from additional modifications in downstream fluxes, for example the transport of carbohydrates to sink tissues ( Wang et al , 2020 ). Modified canopy-scale models that account for Rubisco parameters may help further to predict the physiological consequences of replacing native Rubiscos with heterologous enzymes in plants ( Iqbal et al , 2021 ).…”
Section: Rbcs As An Engineering Target For Enhancing Plant Photosynth...mentioning
confidence: 99%
“…Biochemical models predicted that installing selected C 4 Rubiscos in C 3 plants could improve photosynthesis by more than 25% ( 9 , 35 ). Previous attempts to capture kinetic signatures of C 4 Rubiscos were mostly performed through evolutionary analyses of the L subunits, with limited success ( 6 8 , 10 , 36 , 37 ). Despite multiple lines of evidence showing the influence of both subunits on catalysis ( 16 , 19 , 38 41 ), it is still challenging to carry out large-scale phylogenetic analyses of the S subunits in plants due to the lack of available sequences except in a relatively small number of model species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to comparing the contributions of different adaptations during drought, modelling can provide valuable insights into the ways in which physiological traits interact with different forms of photosynthesis (Iqbal et al , 2021). Our model found that C FT had a substantially smaller effect on gas exchange rates and diel Ψ L in the CAM background, in comparison to the C 3 simulations ( Fig.…”
Section: Discussionmentioning
confidence: 99%